Differential graded categories associated with the critical semi-definite quadratic forms - Gnatiuk, O.; Golovaschuk, N. (Algebra and Discrete Mathematics, 2013)
This work concerns with classification problem of differential graded categories with critical semi-definite quadratic form. We prove that such problem which satisfies some correctness conditions can be transformed to differential graded category with directed graded graph, which is a quiver of affine (extended) type.